A expansão urbana de Tubarão (SC): uma perspectiva semiótica de análise - Piuco, Maria Arlete Goulart (2006)
The main purpose of this work is to analyze the urban expansion of the city of Tubarão from 1990 and its main vectors, starting from two reference documents: verbal documents, constituted of interviews, and non-verbal (aerial photographs), in an interface for geographic analysis (Beaujeu-Garnier, 1997; Lefebvre, 1991) with Charles Peirce’s (1977) and Charles Morris’ (1976) semiotics. It was opted to use Peirce’s and Morris’ Semiotics on the readings of urban evolution of Tubarão because of the great signal diversity of the urban spaces that contribute to the attribution of meaning on the studied context. The analysis of the verbal texts points toward the importance of the referral system of the interpreter and the importance of knowledge to decode the non-verbal texts and identify vectors that contributed to the analyzed urban expansion.